Jeanne D'Arc: Her Life And Death - Oliphant, Mrs. (Margaret), 1828-1897 (Salt Lake City, UT : Project Gutenberg, 2006)
"Jeanne D'Arc: Her Life And Death" by Mrs. Oliphant is a historical account likely written in the late 19th century. This narrative explores the life and legacy of Jeanne D'Arc, also known as Joan of Arc, the iconic French heroine who played a crucial role in the Hundred Years' War. Through her story, Mrs. Oliphant delves into themes of purity, faith, and national identity amidst the tumultuous backdrop of 15th-century France. At the start of the book, the author sets the stage by providing a captivating glimpse into Jeanne's early life in the rural village of Domrémy. The narrative paints a vivid picture of the profoundly troubled state of France during her childhood, marked by civil strife and foreign invasion. The opening also introduces Jeanne's initial experiences with divine voices and visions that would ultimately guide her to believe she was destined to lead France to victory. The text invites readers to witness the transformation of this humble peasant girl into a figure of national importance, foreshadowing the extraordinary journey that will follow as she rises to confront the English oppressor and champion her king. (This is an automatically generated summary.)
Release date is 2006-03-28
Produced by Dagny; and John Bickers and David Widger
Keywords: Joan, of Arc, Saint, 1412-1431; France -- History